Analysis of Marketing Channels for Koi Fish (Cyprinus Carpio) At the Freshwater Ornamental Fish Promotion Center (Case Study, Rawalumbu District, Bekasi City) - Putri Sahrani Alif; Atikah Nurhayati; Ibnu Dwi Buwono; Ine Maulina (Universitas Islam Lamongan, 2024)
This research aims to analyze the marketing channels for koi fish at the UPTD Freshwater Ornamental Fish Promotion Center in Rawalumbu District, Bekasi City. This research was carried out from March 2024 to April 2024 using the snowball sampling method or snowball technique. The parameters analyzed are marketing channels, marketing margins, revenue and cost balance (BCR), and transportation techniques for koi fish. This koi fish marketing channel analysis was carried out at the UPTD Freshwater Ornamental Fish Promotion Center in Rawalumbu District, Bekasi City. Based on the research results, the results showed that the koi fish marketing channel pattern at the UPTD Freshwater Ornamental Fish Promotion Center in Rawalumbu District, Bekasi City has two fish marketing channel patterns. In the channel I pattern, it consists of (cultivators, collectors, wholesalers, retailers and final consumers), channel II (cultivators, collectors, retailers and final consumers). The most efficient marketing channel of the two existing channels is channel II, seen from its revenue and cost balance (BCR) value of 1.3, It is recommended that further research be carried out in this research using a different problem approach method so that information about koi fish marketing can be used better.